2008
DOI: 10.1159/000121399
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Genetic Susceptibility for the Prevention of Colorectal Cancer: A Qualitative Study of Older Adults’ Understanding

Abstract: Objective: To assess whether public understandings of inherited predisposition to colorectal cancer may undermine preparedness to respond to preventive messages. Methods: Structured in-depth interviews with 31 women and men, aged 50 years and over. Results: Most participants viewed genetic factors as prompts for taking preventive measures rather than as reasons for fatalism and inaction. They were optimistic about the potential benefits of new developments in cancer prevention and treatment. Conclusions: There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
(38 reference statements)
1
9
0
1
Order By: Relevance
“…As Lucke et al (13), and Walter et al (14), have found, personal experience with a particular condition further shapes these understandings. Thus, if the person one knows with diabetes has a family history of it, one is more likely to assume that diabetes ‘is hereditary’ than if the person whom one knows with diabetes does not have such a family history.…”
Section: Conceptions Of Hereditary Patterns Are Shaped By Social Expementioning
confidence: 91%
“…As Lucke et al (13), and Walter et al (14), have found, personal experience with a particular condition further shapes these understandings. Thus, if the person one knows with diabetes has a family history of it, one is more likely to assume that diabetes ‘is hereditary’ than if the person whom one knows with diabetes does not have such a family history.…”
Section: Conceptions Of Hereditary Patterns Are Shaped By Social Expementioning
confidence: 91%
“…42,43 Research on lay understanding of health has shown that most Western populations realize that health is a product of variable inputs of both personal behavior and familial inheritance. 36,4451 Evidence supports the public’s nuanced understanding of the role of genetics in health that varies based on the character of the disease, 46,49 the family’s experience with the disease, 52,53 the character of the treatments available, the pathways by which the genes act, 54 and the communication approach used to present genetic risk and behavioral options. 37 Research to identify these human factors more precisely is essential if genomic discoveries and their applications are to be most useful and least harmful.…”
Section: Priority Areas In Communication Behavioral and Social Sciementioning
confidence: 98%
“…Genetic testing for cancer susceptibility has transformed the nature of communication between clinicians and their patients about disease risk, screening, treatment, and prevention strategies. Effective communication with patients about disease risk is important because previous research has demonstrated that one’s risk perception has the potential to positively influence screening behaviors and treatment decisions (Lipkus et al 2000; Lucke et al 2008), both of which may improve health outcomes. Yet, the extent to which lay theories of disease influence the interpretation of genetic information about cancer risk among patients and their families remains largely unanswered.…”
Section: Introductionmentioning
confidence: 99%